Transformational Leadership and Individual Performance in Military Personnel: The Mediating Role of Organizational Trust and Public Service Motivation - Dedyk Wahyu Widodo; Suryanto Suryanto (Institut Agama Islam Sunan Giri Ponorogo, 2026)
This research is driven by the difficulty of boosting the individual performance of military people, especially Babinsa in territorial units, with more complicated tasks. The purpose of this study is to analyse the effect of transformational leadership on individual performance both directly and indirectly through organizational trust and public service motivation as the mediating variables. This study adopts a quantitative technique with a population of 175 Babinsa staff in Kodim 0816/Sidoarjo. The data analysis was accomplished by the PLS-SEM technique using SmartPLS 4 software. The findings of this study show that transformational leadership has a positive and significant effect on individual performance, organizational trust, and public service motivation; organizational trust and public service motivation influence individual performance; furthermore, organizational trust and public service motivation are proven to have a positive and significant mediating effect on the relationship between transformational leadership and individual performance. Theoretically, this study has implications for the development of Social Exchange Theory and the mediating effects of organizational trust and public service motivation in military organizations. Practically, this study provides new insights for leaders in building trust and public service motivation to maximize personnel performance.